Sistem Remote Control dan Monitoring Kendaraan Berbasis Borland Delphi 7 Menggunakan GPS GSM Tracker - Rifki Dwi Faradila (Jurnal Jaringan Telekomunikasi, 2015)
The monitoring program is made running using SMS communication on the GSM network with the aim of its application is to be used to monitor various types of vehicles commonly used by the public as a means of transportation. The GPS that is installed functions as a device that will search for location coordinates in the form of latitude and longitude to be sent to the user. On the user side is given a program that will process any data sent by the GPS device and display it in the form of a digital map as a tool for users to monitor their vehicle.From the test results for the time needed to request the position of the vehicle from the program to the GPS device via SMS, the average time value is 16.11 seconds in each position request. Meanwhile, for testing the accuracy of the vehicle position plot with an average speed of 10km / hour, the difference in distance is +/- 27.5 m, 20km / hour is the difference in the distance +/- 55.1 m, 30km / hour is the difference in the distance +/- 82, 7 m, 40 km / h difference +/- 100.3 m, 50 km / h difference +/- 137.5 m, 60 km / h difference +/- 165.5 m distance, and 70 km / h difference + / -197.1 m.